The Effect Of Capital Structure, Institutional Ownership, And Company Size On Financial Performance - Murti, Galuh Tresna; Faradisyi, Zahra Nelfa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The aim of this study was to determine the effect of capital structure, institutional ownership, and company size on the financial performance of insurance sub-sector companies listed on the Indonesia Stock Exchange in the 2017–2021 period. This data was tested using the panel data regression method. The population used is the insurance companies listed on the IDX in 2017–2021. Based on the sample selection, 15 insurance sub-sector companies were selected for five years period of study. So the total number of observational data in this study was 75. However, only 70 data can be used because there are 5 outliers. The results of this study show that capital structure, institutional ownership, and company size simultaneously influence the company's financial performance. Partially, institutional ownership and company size influence the company's financial performance. While the capital structure does not have any effect on financial performance.